Survival after radiation for stage I and II non-small cell lung cancer with positive margins - (:unkn) unknown (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2018)
Background: There is limited data guiding treatment for positive margins following lobectomy for early-stage non-small cell lung cancer (NSCLC). Using data from the National Cancer Data Base, we sought to determine whether radiation therapy following lobectomy for stage I or II NSCLC was associated with improved overall survival in patients with positive margins. Methods: Patients who underwent lobectomy without induction therapy for stage I or II NSCLC (1998-2006) with positive resection margins were selected. Patients were stratified by administration of radiation therapy following surgery, and overall survival was estimated using the KaplaneMeier method. The association between radiation therapy and survival was adjusted for nonrandom treatment selection using Cox proportional hazards regression modeling. Results: Positive margins were recorded in 1934 of 49,563 (3.9%) patients who underwent lobectomy for stage I or II NSCLC. Positive margin status was associated with significantly worse 5-year survival (34.5% versus 57.2%, P < 0.001). After selection of patients with positive margins and known radiation status and exclusion of patients who had upstaged disease or received radiation therapy for palliative indications, radiation therapy was used in 579 of 1579 patients (38.2%) but was not associated with a significant difference in the likelihood of death during subsequent follow-up (hazard ratio: 1.10, 95% confidence interval: 0.90, 1.35). Conclusions: Positive margins following lobectomy for stage I or II NSCLC are associated with reduced 5-year survival. Postsurgical radiation is not strongly associated with an improvement in overall survival among these patients. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Radiation therapy; Positive margins; Non-small cell lung cancer; Lobectomy; MICROSCOPIC RESIDUAL DISEASE; RESECTION; TUMOR; R1